2007
DOI: 10.1038/ncb1573
|View full text |Cite
|
Sign up to set email alerts
|

The neural progenitor-specifying activity of FoxG1 is antagonistically regulated by CKI and FGF

Abstract: FoxG1 is an evolutionarily conserved, winged-helix transcriptional repressor that maintains progenitor cells in the vertebrate forebrain. How the activity of FoxG1 is regulated is not known. Here, we report that in the developing Xenopus and mouse forebrain, FoxG1 is nuclear in progenitor cells but cytoplasmic in differentiating cells. The subcellular localisation of FoxG1 is regulated at the post-translational level by casein kinase I (CKI) and fibroblast growth factor (FGF) signalling. CKI phosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 35 publications
3
106
0
Order By: Relevance
“…60), growth factor signaling through FGFR4 may play an important role in hepatic insulin action. In support of this idea, FGFR4 knock-out mice have impaired glucose tolerance (67), and transgenic expression of FGF19 reverses diabetes in the leptin-deficient ob/ob mouse (68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60), growth factor signaling through FGFR4 may play an important role in hepatic insulin action. In support of this idea, FGFR4 knock-out mice have impaired glucose tolerance (67), and transgenic expression of FGF19 reverses diabetes in the leptin-deficient ob/ob mouse (68).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we wondered whether the bile acid feedback regulation of hepatic CYP7A1 through intestine-derived FGF15 might also target FoxO1 through PI 3-kinase signaling. In fact, a recent report demonstrated that FGF signaling through PI 3-kinase regulates the related FoxG1 protein in the vertebrate forebrain (60). If the FGF19/15 signaling pathway plays a role in the regulation of CYP7A1 during fasting, then either intestinal FGF15 production or hepatic expression of FGFR4 should be decreased by fasting.…”
Section: Fgf19 Inhibits Expression Of Cyp7a1 and Other Foxo1mentioning
confidence: 99%
“…S2e). RT-qPCR analyses of the isolated cells showed co-expression of neural marker mRNAs (Sox2 and Nestin) 25,26 with Epo mRNA in NEP cells ( Supplementary Fig. S3a).…”
Section: Articlementioning
confidence: 99%
“…The serine phosphorylation status of FOXG1 in ovarian cancer cells was analysed according to Regad et al (2007). Briefly, ovarian cancer cells were collected in NET lysis buffer (50 mM Tris, pH 7.4, 150 mM NaCl and 5 mM EDTA) with 1% NP40, pH 8.0, 0.1 mM PMSF and 1 mM Complete TM protease inhibitor cocktail (Roche).…”
Section: Subcellular Fractionation and Phosphorylation Studiesmentioning
confidence: 99%